Awarding Monopoly Franchises - Riordan, Michael H.; David E. M. Sappington (American Economic Review, 1987)
We explain how to award a monopoly franchise so as to maximize expected consumers' welfare. Potential producers initially possess imperfect private information about production cost. The franchise is awarded to the producer with the lowest expected costs, but prices exceed realized marginal costs. These ex post distortions foster more competitive bidding ex ante. The distortions for any bid-cost pair are invariant to the number of bidders (n), though expected distortions and profits decline with n.